2021
DOI: 10.3389/fmicb.2021.663116
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the Conversion and Extraction of Arctigenin From Fructus arctii Into Arctiin Using Fungi

Abstract: Fructus arctii is commonly used in Chinese medicine, and arctiin and arctigenin are its main active ingredients. Arctiin has low bioavailability in the human body and needs to be converted into arctigenin by intestinal microbes before it can be absorbed into the blood. Arctigenin has antiviral, anti-inflammatory, and anti-tumour effects and its development has important value. In this study, we used external microbial fermentation with Aspergillus awamori and Trichoderma reesei to process and convert arctiin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…and absorbed into the blood (17). Several studies have showed a wide spectrum of pharmacological activity attributed to Arc including neuroprotection, anti-inflammation and anti-oxidative stress properties (18)(19)(20).…”
Section: Arctiin Alleviates Functional Constipation By Enhancing Inte...mentioning
confidence: 99%
“…and absorbed into the blood (17). Several studies have showed a wide spectrum of pharmacological activity attributed to Arc including neuroprotection, anti-inflammation and anti-oxidative stress properties (18)(19)(20).…”
Section: Arctiin Alleviates Functional Constipation By Enhancing Inte...mentioning
confidence: 99%
“…To date, numerous researchers from various countries have investigated MFH (Table 1) (Khan, Huang, et al., 2018; Pinela et al., 2017; Shingnaisui et al., 2018; Xie et al., 2022), which has proven to be an effective means of regulating human health owing to its rich content of natural active ingredients, such as polyphenols, flavonoids, polysaccharides, saponins, alkaloids, and essential oils (Garayev et al., 2018; Lu et al., 2022; Mdkhana et al., 2021; Pan et al., 2021; Zacchino et al., 2017; Zhang, Zhu, et al., 2022). The development of probiotics (Table 2) in recent years has opened up opportunities for MFH, and probiotic‐driven fermentation provides a novel approach to the high‐value and industrialization of MFH, addressing the limitations of its application, such as certain side‐effects, lack of in‐depth studies on its efficacy, low oral bioavailability, and poor flavor (Bohn et al., 2015; Leonard et al., 2021; Lu et al., 2021). In addition, studies have shown that the biological activity of many herbs, including MFH, is achieved through biotransformation by intestinal microbiota (Hussain et al., 2016).…”
Section: Introductionmentioning
confidence: 99%